Voces sobre la desaparición forzada de infantes durante la guerra en El Salvador : archivo para la memoria (1980-1984) - Ocampo Saravia, Tania (Pública memoria ;, 2018)
Systematic look at neglected aspect of human rights abuses committed during brutal 12-year armed conflict in El Salvador. Documents military operations that involved forced disappearance of children (most under 12 years old) that were left out of official report by Truth Commission. Recounts effort by parents, activists and others to investigate disappearances and recover children.